Análise da associação entre fatores psicossociais e o padrão de recrutamento dos músculos abdominais medidos por meio de ultrasonografia em indivídous com dor lombar crônica não-específica - Warley de Melo Oliveira (2007)
Study Design. Cross-sectional study of ultrasound measurement of abdominal muscle activity and psychosocial factors in chronic low back pain (LBP) patients.Objectives. To investigate the association between the psychosocial factors of kinesiophobia, health locus of control, and psychomotor speed and the recruitment of the abdominal muscles transversus abdominis (TrA), obliquus internus (OI), and obliquus externus (OE) measured with ultrasonography in patients with chronic non-specific LBP.Summary of Background Data. Although recruitment of the abdominal muscles and psychosocial factors are important in the management of chronic LBP, it is not known whether they are associated.Methods. Fifty six patients with chronic LBP were included in the study. Abdominal muscles recruitment was measured with ultrasonography in a task that challenged the lumbar spine during isometric contraction of the limbs at low loads. Changes in muscle thickness from resting baseline values were obtained for TrA, OI, and OE. The Tampa scale and the multidimensional heath locus of control (MHCL) questionnaire were used to assess patients kinesiophobia and locus of control towards LBP. Psychomotor speed was measured with a reaction time test. Multiple linear regression models with the three psychosocial factors included were built to test the association with the recruitment of abdominal muscles.Results. The regression models accounted for 11.8 % (R2=0.12; F=0.71; p=0.67), 21.2 % (R2=0.21; F=1,42; p=0,23) and 32,3% (R2=0.32; F=2,52; p=0,03) of the variance of the TrA, OI and OE recruitment respectively. No psychosocial factor was found to be significantly associated with muscle recruitment. Internal locus of control, psychomotor speed and external locus of control tended to be associated with TrA (=.005; p=.08), OI ( =-5.11; p=.09), and OE ( =-.003; p=.09) recruitment respectively.Conclusion. Health locus of control, kinesiophobia, and psychomotor speed explain recruitment of OE but not TrA and OI in LBP. Future studies should investigate the tendency of an association between the recruitment of TrA and internal locus of control, OI and psychomotor speed, and OE and external locus of control.